1971
DOI: 10.1530/jrf.0.0240111
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Frozen Rabbit Semen

Abstract: Summary. Rabbit semen was extended in a tris-yolk-12\m=.\5% DMSO extender and frozen in liquid nitrogen vapour or on a 'dry ice' block after glycerol had been added. No differences (P>0\m=.\10) were found between inseminations with liquid semen and semen frozen in pellets with regard to the number of young born or the pregnancy rate. Other methods produced significantly (P<0\m=.\05) fewer young. Significantly (P<0\m=.\05) more young were born to does inseminated 5 hr after they received the ovulating hormone.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…In this context, the basic ingredients of current sperm-freezing extenders in rabbits are a combination of permeating cryoprotectants such as acetamide or dimethyl sulphoxide (Me 2 SO) and non-permeating cryoprotective agents such as lactose, sucrose, raffinose or trehalose. In addition, egg yolk is often included as an additional protective additive in rabbit sperm-freezing extenders (Fox, 1961;Stranzinger et al, 1971;Mocé and Vicente, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the basic ingredients of current sperm-freezing extenders in rabbits are a combination of permeating cryoprotectants such as acetamide or dimethyl sulphoxide (Me 2 SO) and non-permeating cryoprotective agents such as lactose, sucrose, raffinose or trehalose. In addition, egg yolk is often included as an additional protective additive in rabbit sperm-freezing extenders (Fox, 1961;Stranzinger et al, 1971;Mocé and Vicente, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the generally unsatisfactory results with frozen semen (Stranzinger et al, 1971;Maurer et al, 1976; Hanada and Nagase, 1980; Constantini, 1989;Fargeas, 1995). In order to better utilize semen from males of high genetic value, for production as well as for conservation and genetic programmes, use of frozen semen is important.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol has been extensively used as a cryoprotectant for various cells, including mammalian spermatozoa and embryos, since Polge et al [7] reported its cryoprotective properties. In early research on freezing of rabbit spermatozoa, spermatozoa frozen with glycerol resulted in extremely low fertility [8][9][10][11]. After 1980, studies employing acetamide [12][13][14][15] or DMSO [12,[16][17][18][19][20][21][22] as a cryoprotectant have been encouraging.…”
mentioning
confidence: 99%